The relationship between swallowing training after total laryngectomy and the incidence of pharyngeal fistula a retrospective study with nursing-related insights - Yang, Xi; Jia, Wenbi (Frontiers in Medicine, 2025)
BackgroundPharyngeal fistula (PF), a critical complication in 10%–30% of total laryngectomy (TL) patients, delays recovery and increases healthcare costs. Current guidelines lack consensus on non-surgical prevention strategies, particularly nursing-led interventions. This study introduces an evidence-based structured swallowing training protocol integrating viscosity-modified diets, breath-holding exercises, and sensory stimulation, which was associated with reduced PF risk under systematic nursing supervision.MethodsIn this single-center retrospective cohort study, 430 TL patients were enrolled: 220 received structured swallowing training initiated 10–14 days postoperatively (3×/day for 4 weeks), while 210 received standard care. The intervention comprised (1) diet progression with dry swallowing exercises, (2) seated breath-holding to trigger glottic closure, (3) tongue resistance and laryngeal elevation, and (4) sensory stimulation (preoperative taste activation, intraoperative pharyngeal brushing, postoperative imagery). Primary outcomes were PF incidence and severity; multivariate logistic regression was used to identify independent predictors (adjusted OR, 95% CI).ResultsSwallowing training was associated with a 34.2% lower PF incidence (10.0% vs. 15.2%, P = 0.034) and fewer severe cases (68.2% mild vs. 37.5%, P = 0.021). Multivariate analysis confirmed training as an independent protective factor (adjusted OR = 0.55, 95% CI = 0.32–0.95, P = 0.031), while intraoperative blood loss ≥ 400 mL was an independent risk factor (adjusted OR = 1.75, 95% CI = 1.02–3.00, P = 0.043). Adherence was high (84.1%), and protocol fidelity reached 98.6%.ConclusionNursing-led structured swallowing training was independently associated with a 45% lower risk of PF after TL, providing a scalable and cost-effective rehabilitation framework that underscores the essential role of nursing in postoperative complication prevention.